A crise do direito na concepção de Boaventura de Sousa Santos - Azor, Eliane da Costa Ribeiro (2008)
Whether the law can be emancipator is the question this text proposes to answer from the point of view of Boaventura de Sousa Santos. The approach is to analyze the conditions of the crisis in law in capitalist societies since it was transformed in a kind of state and scientific law and has been the only form of law validates in those societies. In response, the author proposes a new use of the law, through the cosmopolitan subaltern legality. A law capable of serving the subalterns movements as an instrument of social emancipation